2022
DOI: 10.5194/acp-22-6275-2022
|View full text |Cite
|
Sign up to set email alerts
|

A process-oriented evaluation of CAMS reanalysis ozone during tropopause folds over Europe for the period 2003–2018

Abstract: Abstract. Tropopause folds are the key process underlying stratosphere-to-troposphere transport (STT) of ozone, and thus they affect tropospheric ozone levels and variability. In the present study we perform a process-oriented evaluation of Copernicus Atmosphere Monitoring Service (CAMS) reanalysis (CAMSRA) O3 during folding events over Europe and for the time period from 2003 to 2018. A 3-D labeling algorithm is applied to detect tropopause folds in CAMSRA, while ozonesonde data from WOUDC (World Ozone and Ul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Recent NASA coupled chemistry-meteorology products are likewise promising for studying stratospheric intrusions (MERRA2-GMI [Global Modeling Initiative] and GEOS-CF [Goddard Earth Observing System Composition Forecasts]; Strode et al, 2015;Keller et al, 2021;Knowland et al, 2022). CAMSRA ozone is broadly consistent with upper-tropospheric observations during stratospheric intrusions over Europe, despite overestimation in some sites (Akritidis et al, 2022), and lower-tropospheric ozone in East Asia (Park et al, 2020). Stratospheric ozone in CAMSRA is parameterized using the Cariolle scheme (Cariolle & Déqué, 1986;Cariolle & Teyssèdre, 2007), and subject to data assimilation.…”
Section: Methodsmentioning
confidence: 91%
“…Recent NASA coupled chemistry-meteorology products are likewise promising for studying stratospheric intrusions (MERRA2-GMI [Global Modeling Initiative] and GEOS-CF [Goddard Earth Observing System Composition Forecasts]; Strode et al, 2015;Keller et al, 2021;Knowland et al, 2022). CAMSRA ozone is broadly consistent with upper-tropospheric observations during stratospheric intrusions over Europe, despite overestimation in some sites (Akritidis et al, 2022), and lower-tropospheric ozone in East Asia (Park et al, 2020). Stratospheric ozone in CAMSRA is parameterized using the Cariolle scheme (Cariolle & Déqué, 1986;Cariolle & Teyssèdre, 2007), and subject to data assimilation.…”
Section: Methodsmentioning
confidence: 91%
“…This downward transport leads to changes in tropospheric ozone levels (Xiong et al, 2022). An increase in tropospheric O 3 level is observed during the folding events, which have a stratospheric origin (Akritidis et al, 2022). Akriditis et al identified changes in tropopause fold frequencies from 1970-1999 to 2070-2099 in both hemispheres, regionally exceeding 3%, and found links with the projected changes in the position and intensity of the subtropical jet streams (Akritidis et al, 2019).…”
Section: Stratosphere-troposphere Exchange (Ste)mentioning
confidence: 99%